2018
DOI: 10.18203/2320-1770.ijrcog20182889
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of knowledge and practices of menstrual hygiene among urban adolescent girls in North India

Abstract: Background: Menstruation and menstrual practices are still associated with   socio-cultural restriction and taboos which results lack of knowledge and awareness in adolescent girls and remain ignore of scientific facts and hygienic practices during menstruation leads to severe reproductive health problems. The aim of the study is to assess the knowledge and menstrual hygiene practices among urban adolescent girls.Methods: A cross sectional observational study conducted. Total 120 adolescent girls enrolled in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
2
1
Order By: Relevance
“…The result of the present study showed that majority of adolescent girls had moderate practice during menstruation. The present study result was contradicted by the study conducted by Gandotra N et al, Uttarkhand, India who reported majority of participants knew about menstruation from mothers and showed adolescent girls had good practice during menstruation [8].…”
Section: Volume 3 • Issue 1 • 1000123contrasting
confidence: 99%
“…The result of the present study showed that majority of adolescent girls had moderate practice during menstruation. The present study result was contradicted by the study conducted by Gandotra N et al, Uttarkhand, India who reported majority of participants knew about menstruation from mothers and showed adolescent girls had good practice during menstruation [8].…”
Section: Volume 3 • Issue 1 • 1000123contrasting
confidence: 99%
“…Another barrier to a comfortable and dignified experience of MHM among girls was the lack of or limited awareness as reported in 92 studies (Table 2) [16,18,[23][24][25][26]31,[33][34][35][36][37][39][40][41][42][43][44]48,49,[51][52][53][54][55]57,58,[62][63][64][65][67][68][69][70][71]77,78,[80][81][82][83][84][85]87,89,90,92,93,95,…”
Section: Girls' Awareness Of Mhmmentioning
confidence: 99%
“…In the present study, 57% of the adolescent girls had awareness about menstruation before menarche, which is similar to the study conducted in West Bengal, where 67.5%, and in Uttarakhand, where 62.5% of girls were aware of menstruation prior to attainment of menarche. [ 3 14 ] However, it was observed to be low, around 24%, in the study conducted by Deshpande et al . [ 2 ] and only 18.67% in the study by Zaidi et al .…”
Section: Discussionmentioning
confidence: 99%